Angels among us? The Watchers myth and angelology in Ephrem's Commentary on Genesis and the Ethiopic tradition - Skelton, David A (Journal for the study of the pseudepigrapha, 2019)
This study examines the euhemeristic interpretation of Genesis 6:1-4 as it appears in Ephrem of Nisibis' Commentary on Genesis and its influence on Syriac and Ethiopic commentary traditions. I suggest that Ephrem's attempt to mitigate the angelic interpretation of Genesis 6 ironically mirrors his own angelology. The distinctive components he adds to the Watchers myth (different geography, diet, and bodies) are central virtues in Ephrem's attempt to make virginity and monasticism ideals for all Christians. For Ephrem, the angels are paradigms of these ideals, and those who achieve them become equal to the angels. Surprisingly, these distinctive components reappear in the Ethiopian commentary tradition on Genesis (andemta), but unlike Ephrem, the andemta makes the equation of Sethites with angels and monks quite explicit. Overall, this analysis between Ephrem and the andemta reveals the influence of Syriac interpretation on the Ethiopian commentary tradition as well as the centrality of angelology in the Sethite reading of Genesis 6:1-4.